PSYCHOLOGICAL DIMENSIONS AND PEDAGOGICAL SKILLS IN DEVELOPING PANCASILA BASED HUMANISTIC VALUES FOR STUDENTS IN INDONESIA. - Nuraya, Nuraya; Ismail, Nik Ahmad Hisham; Saad, Muhammad Azannee (FORUM PAEDAGOGIK, 2025)
The Indonesian Ministry of Education has implemented a new curriculum, the Merdeka curriculum. This new curriculum emphasizes student-centered teaching and learning activities. However, problems and issues in the teaching of Psychology, Pedagogy, and Pancasila continue and are consistent. This study aims to explore teachers' understanding of methods and experiences in learning how to improve students' humanistic values based on Pancasila, and linked to the Merdeka curriculum. This is qualitative research. Case studies were conducted using participant observers and investigators. A total of 6 informants were selected by purposive sampling. The sample consisted of 2 Psychology teachers (counseling), 2 PPKN teachers (Pancasila), and 2 pedagogy teachers. Data were obtained through interviews, classroom observations, semi-structured interviews, and document analysis. The findings show that teachers have a very good understanding of the concept of differentiation in the Merdeka curriculum; however, teachers experience obstacles and difficulties in their practice and in implementing Pancasila values because the independent curriculum implemented does not influence students' attitudes toward these humanistic values. Therefore, this study suggests that teachers' teaching methods and strategies for learning students' Humanistic values need to be improved and fully supported by schools.